1998
DOI: 10.1063/1.475519
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculation for potential energy surfaces relevant to the microscopic reaction pathways for Mg(3s3p1P1)+H2→MgH(2Σ+)+H

Abstract: Two ab initio methods have been employed to calculate the dynamical potential energy surfaces (PES’s) for the excited (B21 or A'1) and the ground (A11 or A'1) states in the Mg(3s3p1P1)–H2 reaction. The obtained PES’s information reveals that the production of MgH in the Σ+2 state, as Mg(1P1) approaches H2 in a bent configuration, involves a nonadiabatic transition. The MgH2 intermediate around the surface crossing then elicits two distinct reaction pathways. In the first one, the bent intermediate, affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…They have concluded that the intermediate would live long enough to redistribute its internal energies, and the (MgD 2 )* intermediate has a longer lifetime than the (MgH 2 )* intermediate (probably due to the larger reduced mass of the former). A stable (MgH 2 )*, made from Mg(3s3p, 1 P) has been confirmed later by a calculation by Ou et al A work by Ohmori et al on the Hg(6s6p, 3 P 1 ) + H 2 also suggested the existence of an intermediate. The collision path leading to these intermediates may evolve during a relatively long rovibrational lifetime before resulting in an inelastic quenching or a reaction.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…They have concluded that the intermediate would live long enough to redistribute its internal energies, and the (MgD 2 )* intermediate has a longer lifetime than the (MgH 2 )* intermediate (probably due to the larger reduced mass of the former). A stable (MgH 2 )*, made from Mg(3s3p, 1 P) has been confirmed later by a calculation by Ou et al A work by Ohmori et al on the Hg(6s6p, 3 P 1 ) + H 2 also suggested the existence of an intermediate. The collision path leading to these intermediates may evolve during a relatively long rovibrational lifetime before resulting in an inelastic quenching or a reaction.…”
Section: Discussionmentioning
confidence: 73%
“…In the second category belong the Mg* + H 2 /D 2 case ,, and the Na* + H 2 /HD/D 2 case 20 where bimodal rotational structures have been observed for both AH and AD (with some differences for the large J between the MgH and MgD, while no such differences were found for the NaH and NaD). This was supposed to result from predominantly side-on attack ( C 2 v ) leading to an insertion rather than a collinear (or end-on) attack leading to an abstraction.…”
Section: Discussionmentioning
confidence: 99%
“…20 Taking account of the zero-point energy yields 12 and somewhat smaller than a more recent estimate of 0.51 eV (11.8 kcal/mol) reported by Ou and co-workers. 36 The other MgH 2 decomposition channel, namely, MgH 2 f MgH + H, is predicted to be strongly endothermic by 3.1786 eV (73.30 kcal/mol) and 3.1580 eV (72.83 kcal/mol) at the CBS(V) and CBS(V+C) levels of theory, respectively, with no barrier on the reaction path. The calculated relative energies of various dissociation limits and of the transition state (relative to the triatomic potential minimum) at different levels of theory are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…Among the reactions of alkaline earth atoms with H 2 , Mg has drawn the most attention thus far. The reaction of Mg(3s3p 1 P 1 ) with H 2 has been studied for more than a decade. Breckenridge and co-workers first found the bimodality for the rotational distributions of MgH( v =0 and 1), with the major components (∼90%) peaking at very high quantum numbers and the minor components at approximately N = 10. , A value of 0.7 ± 0.2 was reported for the ratio of the population of v = 1 and v = 0. The reaction pathway leading to the high- N distribution was considered to originate from Mg insertion into the H 2 bond, such that one H atom release from the bent complex would induce a large torque to cause rotational excitation of the product.…”
Section: Introductionmentioning
confidence: 99%
“…Since the same intermediate is responsible for the two distinct rotational and vibrational distributions, the current reaction cannot be interpreted in terms of impulsive model . However, by invoking the three- dimensional PESs information provided by a complete active space self-consistent field (CASSCF) calculation level, one may appropriately interpret the reaction pathways involved . As Mg(3 1 P 1 ) approaches H 2 in a bent configuration along the 1 B 2 or 1 A‘ state, the collision complex crosses nonadiabatically to the ground state and then decomposes following two microscopic pathways.…”
Section: Introductionmentioning
confidence: 99%